2006
DOI: 10.1300/j455v01n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Pregnancy

Abstract: This lesson helps participants examine their own attitudes and feelings about being faced with an unplanned pregnancy and understand the difficult choices involved when women need to make a decision William J. Taverner, MA, is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One content area in which innovative teaching methods could be applied is contraceptives. Peer-led education has been increasingly used (Beshers, 2007; DeMairo, Dischell, Jouthe, & Horner, 2007), along with role-play activities (Taverner & Brick, 2006), games (Gilliam, Jagoda, Heathcock, & Sutherland, 2014; Rosenthal, 2010), and video clips (Herrman, Moore, & Anthony, 2012), to teach students about contraceptives. Although previous research has shown the utility of these methods, there is still a disconnect among students knowing how to use contraceptives compared to where they can obtain them.…”
mentioning
confidence: 99%
“…One content area in which innovative teaching methods could be applied is contraceptives. Peer-led education has been increasingly used (Beshers, 2007; DeMairo, Dischell, Jouthe, & Horner, 2007), along with role-play activities (Taverner & Brick, 2006), games (Gilliam, Jagoda, Heathcock, & Sutherland, 2014; Rosenthal, 2010), and video clips (Herrman, Moore, & Anthony, 2012), to teach students about contraceptives. Although previous research has shown the utility of these methods, there is still a disconnect among students knowing how to use contraceptives compared to where they can obtain them.…”
mentioning
confidence: 99%